Oriental Dreams. Reimagining Paradise in the Urban Context (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2024)
The integration of gardens into the urban fabric of Muslim cities has a rich historical background, dating back to the early days of Islam and influenced by classical and Persian cultures that cherished the idea of incorporating gardens into urban designs. As a result, gardens became an inseparable aspect of Muslim cities, intricately woven into their urban structures. This architectural trend extended far beyond geographical boundaries, spanning vast regions of the Muslim empire from Arabia, Greater Syria, and North Africa to Spain, Iran, and India. Gardens held a profound and symbolic importance for Muslims, closely intertwined with their religious beliefs. The Quran, the sacred scripture of Islam, frequently referred to the concept of ‘gardens’, assuring followers of the prospect of dwelling in lush gardens in the realm of paradise. This heavenly vision inspired the creation of earthly gardens, providing a tangible way to experience and connect with the essence of paradise during mortal life. Islamic gardens emerged as a quintessential element of Muslim cities, embodying the values and aesthetics of Islamic culture. Beyond their visually stunning appearance, these gardens also served practical purposes, offering shelter from the sun, refreshing water features, and ample space for social gatherings. This article aims to explore the significance of gardens in Islam, delving into their embodiment of the promised paradise. It will trace the origins of these gardens, examine their diverse forms, analyze their spatial organization, and unravel their multifaceted functions within the landscapes of Muslim medinas. Keywords: Muslim cities, Islamic culture, Quran, urban grid, landscape design